Which Gospel? The Militarization of Sacred Texts in Israel’s Genocide in Gaza - Alkhouri, Yousef Kamal (International journal of public theology, 2024)
Sacred texts have frequently been used to legitimize the oppression and extermination of native peoples. This article argues that Christian and Jewish Zionism, being the ideology of settler-colonialism of Palestine, is genocidal. It showcases the ways sacred texts have been militarized to justify the Zionist settler-colonialism in its genocidal war against the Palestinians. Further, the Israeli military has deployed an Artificial Intelligence military system called ‘the Gospel’. This article poses the question: Which ‘gospel’ would Palestinians think of when they hear this word – that of the Kingdom or of genocide? Applying an empire criticism approach, the article shows the concept carries several connotations – imperial and counter-imperial. The earlier is the imperial ‘Gospel’ of genocide, the latter is the gospel of the kingdom, which is counter-imperial. The church, as an agent of the gospel of kingdom, has to be prophetic in the face of oppression.